Pengembangan Sistem Pengelolaan Acara dengan Pendekatan Gamification - Ericko Wicaksono; Bayu Priyambadha; Fajar Pradana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Current events are very often carried out in different durations, and spheres. Therefore, event management is very important. The management of the programs that are currently available is still not good because of the lack of technology. This problem has an impact on the lack of interest from the event management. In addition, additional interest and enthusiasm from the event management is very necessary. Then to improve additional interest and enthusiasm from the event manager an approach was taken in the form of gamification in managing the event. Gamification has several elements such as badge systems, quests, voting, ranking, and awards. Therefore an event management application was made with a website-based. The application is added gamification approach to facilitate event management. Applications are made using the Springboot and Vue framework. The results of this study are three actors, thirty-seven functional and one non-functional need. Also, the test results are valid.